Current understanding of the molecular mechanisms of circulating permeability factor in focal segmental glomerulosclerosis - Salfi, Giuseppe; Casiraghi, Federica; Remuzzi, Giuseppe (Frontiers in Immunology, 2023)
The pathogenetic mechanisms underlying the onset and the post-transplant recurrence of primary focal segmental glomerulosclerosis (FSGS) are complex and remain yet to be fully elucidated. However, a growing body of evidence emphasizes the pivotal role of the immune system in both initiating and perpetuating the disease. Extensive investigations, encompassing both experimental models and patient studies, have implicated T cells, B cells, and complement as crucial actors in the pathogenesis of primary FSGS, with various molecules being proposed as potential "circulating factors" contributing to the disease and its recurrence post kidney-transplantation. In this review, we critically assessed the existing literature to identify essential pathways for a comprehensive characterization of the pathogenesis of FSGS. Recent discoveries have shed further light on the intricate interplay between these mechanisms. We present an overview of the current understanding of the engagement of distinct molecules and immune cells in FSGS pathogenesis while highlighting critical knowledge gaps that require attention. A thorough characterization of these intricate immune mechanisms holds the potential to identify noninvasive biomarkers that can accurately identify patients at high risk of posttransplant recurrence. Such knowledge can pave the way for the development of targeted and personalized therapeutic approaches in the management of FSGS.